The effect of Merchandising, Price Discount, and Store Atmosphere on Impulse Buying with Positive Emotion as a mediating variable based on Islamic Business Perspective - Ismi Zahra Fadila Yusuf; Femei Purnamasari; Is Susanto (CV. Civiliza Publishing, 2025)
This study aims to describe the phenomenon and also examine the causal relationship that is structured by using a scientific approach and quantitative analysis that is valid and reliable. This study was conducted using quantitative methods. In the context of this study, the population in question is all Alfamart consumers who are in the District Sukarame, Bandar Lampung, which is actively engaged in purchasing activities in Alfamart outlets scattered in the area. The number of samples used in this study is as many as 96 respondents who are domiciled in the city of Bandar Lampung, especially Alfamart consumers in the Sukarame Sub-District. Based on the results of the study, it can be concluded that positive emotions are the main driving factor for impulsive purchases in consumers. Although marketing strategies such as merchandising, price discounts, and store atmosphere have no direct influence, their impact on impulse buying is mediated through the positive emotions they elicit. This finding is also in line with the Islamic business perspective, which views that excessive promotion to manipulate consumer emotions and encourage waste is an unethical practice.